Molecular characterization of a ring X chromosome in a male with short stature - Ellison, Jay W.; Tekin, Mustafa; Sikes, Karen; Yankowitz, Jerry; Shapiro, Lawrence A.; Rappold, Gudrun; Neely, Kirk E. (Human genetics, 2002)
We report the molecular characterization of a ring X chromosome that was transmitted from a mother to a male who has short stature and minor dysmorphic features. This represents only the second reported ring X chromosome in a male. The ring is derived from breakage within the Xp pseudoautosomal region (PAR) and just proximal to the Xq PAR. The total amount of deleted material is 700-900 kb DNA and includes six known transcribed genes. Interestingly, SHOX, a gene implicated in short stature, is not deleted from the ring chromosome. Possible pathogenetic explanations for the patient’s clinical features include insufficient dosage of deleted genes, a position effect on SHOX expression, and cell death during development because of ring chromosome nondisjunction. The findings are also relevant to observations made of "complete" ring chromosomes.